Genomic Characteristics of Bifidobacterium thermacidophilum Pig Isolates and Wild Boar Isolates Reveal the Unique Presence of a Putative Mobile Genetic Element with tetW for Pig Farm Isolates - Tsuchida, Sayaka; Maruyama, Fumito; Ogura, Yoshitoshi; Toyoda, Atsushi; Hayashi, Tetsuya; Okuma, Moriya; Ushida, Kazunari (Frontiers in Microbiology, 2017)
Genomic analysis was performed on seven strains of Bifidobacterium thermacidophilum, a Sus-associated Bifidobacterium. Three strains from the feces of domestic pigs (Sus scrofa domesticus) and four strains from the rectal feces of free-range Japanese wild boars (S. s. scrofa) were compared. The phylogenetic position of these isolates suggested by genomic analyses were not concordant with that suggested by 16S rRNA sequence. There was biased distribution of genes for virulence, phage, metabolism of aromatic compounds, iron acquisition, cell division, and DNA metabolism. In particular four wild boar isolates harbored fiber-degrading enzymes, such as endoglucanase, while two of the pig isolates obtained from those grown under an intensive feeding practice with routine use of antimicrobials, particularly tetracycline harbored a tetracycline resistance gene, which was further proved functional by disk diffusion test. The tetW gene is associated with a serine recombinase of an apparently non-bifidobacterial origin. The insertion site of the tetW cassette was precisely defined by analyzing the corresponding genomic regions in the other tetracycline-susceptible isolates. The cassette may have been transferred from some other bacteria in the pig gut.